2022
DOI: 10.3389/fimmu.2022.943090
|View full text |Cite
|
Sign up to set email alerts
|

A score of DNA damage repair pathway with the predictive ability for chemotherapy and immunotherapy is strongly associated with immune signaling pathway in pan-cancer

Abstract: DNA damage repair (DDR) is critical in maintaining normal cellular function and genome integrity and is associated with cancer risk, progression, and therapeutic response. However, there is still a lack of a thorough understanding of the effects of DDR genes’ expression level in cancer progression and therapeutic resistance. Therefore, we defined a tumor-related DDR score (TR-DDR score), utilizing the expression levels of 20 genes, to quantify the tumor signature of DNA damage repair pathways in tumors and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…GO and KEGG enrichment analysis revealed that FANCD2 -related genes are involved in numerous potential pathways, particularly in cell cycle and DDR pathways. The DDR process plays a significant role in cancer susceptibility, progression, and response to treatment [ 45 ]. The FA pathway, which is activated in response to DNA damage, can maintain genomic stability during the DDR to prevent cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…GO and KEGG enrichment analysis revealed that FANCD2 -related genes are involved in numerous potential pathways, particularly in cell cycle and DDR pathways. The DDR process plays a significant role in cancer susceptibility, progression, and response to treatment [ 45 ]. The FA pathway, which is activated in response to DNA damage, can maintain genomic stability during the DDR to prevent cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the NISCH so far described biological roles [ 7 12 ], and regardless of the tumor type, decreased NISCH expression was associated with activation of metabolic pathways that allow increased tumor growth. In addition, in “NISCH low” phenotype, regardless of the prognostic role, pathways that characterize survival in hypoxic and nutrient deprived conditions like reactive oxygen species pathway, unfolded protein response [ 82 ], and DNA repair [ 83 ], were enriched. This is in line with our finding that nischarin levels are lower in most cancers compared to healthy tissues, since these are critical events for tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The HRD scores of 258 ecDNA+ and 2383 ecDNA-samples among 12 tumor types were compared (except for LGG and OV, because there are no LGG and OV samples mapped to our data). DDR score is a method to quantify the tumor signature of DNA damage repair pathways and was calculated based on the previous study 42 . We used 20 genes they provided (POLQ, EXO1, EME1, BRIP1, FANCA, BLM, FANCI, BRCA2, XRCC2, RAD51, DLX5, UBE2T, BRCA1, FANCB, FANCD2, FEN1, XRCC3, BARD1, GEN1 and PRKDC) as a tumor-related core DDR gene set 42 .…”
Section: Mutation Detection and Heterogeneity Calculation Of Tcga Sam...mentioning
confidence: 99%
“…DDR score is a method to quantify the tumor signature of DNA damage repair pathways and was calculated based on the previous study 42 . We used 20 genes they provided (POLQ, EXO1, EME1, BRIP1, FANCA, BLM, FANCI, BRCA2, XRCC2, RAD51, DLX5, UBE2T, BRCA1, FANCB, FANCD2, FEN1, XRCC3, BARD1, GEN1 and PRKDC) as a tumor-related core DDR gene set 42 . Gene Set Variation Analysis (GSVA) analysis was implemented in R package GSVA (v1.38.2) 43 to calculate DDR scores based on this core DDR gene set for each TCGA sample.…”
Section: Mutation Detection and Heterogeneity Calculation Of Tcga Sam...mentioning
confidence: 99%